Could the Evaluation of Left Ventricular Filling Pressures by Mitral Doppler Predict the Respiratory or Hemodynamic Consequences of Volume Expansion? - Bénédicte Zerr; Nicolas Terzi; Nicholas Sedillot; Fabienne Prieur; Carole Schwebel; Vincent Peigne (Journal of Clinical Ultrasound, 2026)
ABSTRACT Background Many physicians assess left ventricular filling pressures (LVFP) with mitral Doppler before prescribing fluid infusion, in the hope of avoiding the occurrence of a deterioration of oxygenation. This work questions the merits of this practice. Patients and Methods Inclusion criteria were: adult patient receiving mechanical ventilation and vascular filling. Clinical and echocardiographic parameters were collected before and after volume expansion. Patients with increased LVFP (identified by at least one mitral Doppler criterion: E / E ′ > 10 or E / A ≥ 2 or deceleration time < 120 ms) were compared to those without increased LVFP. Primary endpoint was the frequency of a ≥ 15% decrease in the SpO 2 /FiO 2 ratio. Secondary outcome was the response to volume expansion (a ≥ 15% increase in cardiac output). Results Eighty‐seven patients were included in 3 centers with 26 (30%) having elevated LFVP. Only two (2%) patients, who had no increased LVFP, showed respiratory deterioration. The response to volume expansion was identical in patients with or without increased LVFP (25% and 23%, p = 0.8). Conclusion This pragmatic but underpowered prospective study does not support the hypothesis that ultrasound assessment of LVFP by mitral Doppler is a reliable index to predict the respiratory and hemodynamic consequences of filling. Additional studies are required.